2006
DOI: 10.1292/jvms.68.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin II Type 1 Receptor Blocker on Cardiac Angiotensin-Converting Enzyme and Chymase-Like Activities, and Cardiac Fibrosis in Cardiomyopathic Hamsters

Abstract: ABSTRACT. It has been reported that cardiac chymase has an effect on cardiac fibrosis through the Angiotensin (Ang) II formation and an Ang II-independent mechanism. In the present study, Ang II type 1 (AT1) receptor blocker (candesartan cilexetil) was administered to dilated cardiomyopathic (DCM; Bio TO2) hamsters for 4 weeks to study the effect of AT1 receptor blocker on cardiac chymase-like activity and cardiac fibrosis. Echocardiography, histological examination, and assessment of cardiac angiotensin-conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Sympathetic activation is known to induce inflammatory and apoptotic processes and is associated with adverse cardiac events [ 42 , 43 ]. Inhibition of the RAAS significantly reduces cardiac fibrosis [ 44 ]. These findings might suggestthat reduced adrenergic activation might be associated with improved cardiac outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic activation is known to induce inflammatory and apoptotic processes and is associated with adverse cardiac events [ 42 , 43 ]. Inhibition of the RAAS significantly reduces cardiac fibrosis [ 44 ]. These findings might suggestthat reduced adrenergic activation might be associated with improved cardiac outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Its enzymatic hydrolysis product Ang II acts through AT1R to activate fibroblast proliferation and differentiation, resulting in cellular matrix fibrosis in the heart, , eventually leading to ventricular remodeling and cardiac fibrosis . Clinically, the use of ACE inhibitors or angiotensin receptor blockers to suppress RAS is an effective therapy for treatment of cardiac fibrosis . ACE2, the homologue of ACE, generates Ang-(1–9), which, in turn, is further metabolized to Ang-(1–7) by other peptidases, and also directly hydrolyzes Ang II to Ang-(1–7), an antifibrosis factor that can reduce fibrous tissue deposition .…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigators did not show the effect of ARB alone, which has been reported recently to have no effect on cardiac ACE activity in dilated cardiomyopathic hamsters. 43 In humans, a lack of inhibitory effect of simvastatin on plasma ACE activity has been reported. 44 Further studies are needed to clarify the role of statin on ACE activity in the setting of chronic glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%